2011
DOI: 10.1007/s11274-011-0783-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidizing and non-oxidizing biocides on biofilm at different substrate levels in the model recirculating cooling water system

Abstract: With the reducing of water resources, using advanced treated refinery wastewater as recirculating cooling water is an effective method to save water and to reduce the pollution of petroleum and petrochemical industry. However, the control of biofilm is a bottleneck in the application of this technology. To resolve the problem of biofilm formation and development, antimicrobial characteristics of chlorine dioxide and benzyldimethyldodecyl-ammonium chloride on biofilm at different substrate levels were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In recent years, more attention has been paid to the reuse of refinery wastewater in the petroleum industry after advanced treatment (Liu et al, 2011a(Liu et al, , 2011b. Compared with natural water, there are a considerable number of inorganic ions and organic substrates in refinery wastewater, which would lead to easier scale formation in circulating cooling water systems (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more attention has been paid to the reuse of refinery wastewater in the petroleum industry after advanced treatment (Liu et al, 2011a(Liu et al, , 2011b. Compared with natural water, there are a considerable number of inorganic ions and organic substrates in refinery wastewater, which would lead to easier scale formation in circulating cooling water systems (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Benzyldimethyldodecyl ammonium chloride (BDMDAC) is a quaternary ammonium salt agent and cationic biocide, routinely used as a disinfectant in swimming pools and industrial cooling water systems (Ferreira et al 2009;Liu et al 2011). BDMDAC forms an electrostatic bond with the negatively charged sites on microbial cell walls, causing cell lysis, disruption of cell-wall permeability, and reduced intake of nutrients to the cell (Liu et al 2011). BDMDAC has very good inactivation potential, but Gomes et al (2014) concluded that it was unsuccessful at removing biofilms.…”
Section: Benzyldimethyldodecyl Ammonium Chloridementioning
confidence: 99%
“…To control biocorrosion, various techniques have been employed, including protective coatings [ 20 ], corrosion inhibitors [ 21 ], cathodic production [ 22 , 23 ], biological approaches [ 24 ], and biocides [ 25 , 26 ]. Among these methods, all of which are based on the inhibition of bacterial growth and excessive biofilm formation, biocides are the most commonly used.…”
Section: Introductionmentioning
confidence: 99%